Review of 3D Printed Millimeter-Wave and Terahertz Passive Devices - Bing Zhang; Wei Chen; Yanjie Wu; Kang Ding; Rongqiang Li (International Journal of Antennas and Propagation)
The 3D printing technology is catching attention nowadays. It has certain advantages over the traditional fabrication processes. We give a chronical review of the 3D printing technology from the time it was invented. This technology has also been used to fabricate millimeter-wave (mmWave) and terahertz (THz) passive devices. Though promising results have been demonstrated, the challenge lies in the fabrication tolerance improvement such as dimensional tolerance and surface roughness. We propose the design methodology of high order device to circumvent the dimensional tolerance and suggest specific modelling of the surface roughness of 3D printed devices. It is believed that, with the improvement of the 3D printing technology and related subjects in material science and mechanical engineering, the 3D printing technology will become mainstream for mmWave and THz passive device fabrication.